Results of treatment and analysis of prognostic factors in adult patients with Ewing’s sarcoma at the material of Center of Oncology in Cracow - Kokoszka, Anna; Sas-Korczyńska, Beata; Korzeniowski, Stanisław (Contemporary Oncology/Współczesna Onkologia, 2007)
Aim: The aim of this study is to present the results of treatment of Ewing’s sarcoma in adults at the Centre of Oncology in Cracow between 1970 and 2001. Materials and methods: There was a group of 25 adult patients: 19 males (76%) and 6 females (24%). The median age was 19 years (range: 16-42 years). In 52 patients (52%) the primary tumour was located in bones of the pelvis. At the moment of diagnosis 11 patients (44%) had metastatic disease, predominantly lung metastases. Three patients underwent surgery. All patients were given chemotherapy, and 24 patients (96%) received radiation too. In 17 patients (71%) radical radiotherapy was performed. Results: After the treatment complete regression of the tumour was achieved in 8 patients (32%). In 3 patients (12%) a partial response was obtained. Eight patients (32%) developed metastatic disease, and in 6 patients (24%) local progression was observed. Progression-free survival (PFS) and overall survival (OS) for the entire group was 20% at 5 years. In the group of 17 patients (71%) treated with radical radiation PFS and OS survival rate was 29.4 % at 5 years. An analysis of prognostic factors showed that younger age adversely affected overall survival. Better survival was found in males and in patients with localization in extremities. Analysis of therapeutic factors showed that resection of primary tumour significantly improved the results of treatment. Multiagent chemotherapy, radiation with use of 2 opposite fields and application of high dose in the tumour volume were associated with higher PFS and OS rates but differences were not statistically significant.